Hypertrophic cardiomyopathy in combination with juvenile amaurotic idiocy. Chance or fundamentally related findings? - Baandrup, U (1984)
Hypertrophic cardiomyopathy and juvenile amaurotic idiocy (one of the ceroid lipofuscinoses ) were diagnosed in a 29 year old man. This combined finding may be one of pure coincidence, but hypertrophic cardiomyopathy like changes of the myocardium are known to occur in Friedreich's ataxia and lentiginosis . The occurrence may, therefore, indicate some fundamental interrelation.